Characterization of the microbiota of the skin and oral cavity of Oreochromis niloticus Caracterização da microbiota da pele e cavidade oral de Oreochromis niloticus doi:10.12662/2317-3076jhbs.v4i3.767.p193-197.2016 - Lima Junior, Edmar Maciel; Bandeira, Tereza de Jesus Pinheiro Gomes; Miranda, Marcelo José Borges de; Ferreira, Guilherme Emilio; Parente, Ezequiel Aguiar; Piccolo, Nelson Sarto; de Moraes Flho, Manoel Odorico (Journal of Health & Biological Sciences, 2016)
Introduction: Fish are usually exposed to higher microbial loads than land or air animals. The microbiota of fish mostly consists of Pseudomonas spp., Aeromonas spp., Shewanella putrefasciens, Acinetobacter spp. and Moraxella spp. The objective of this study was to analyze the oral cavity, and skin tissue microbiota on the Nile tilapia (Oreochromis niloticus), a fish species raised commercially in Brazil. Methods: Samples were collected from the oral cavity and skin of 20 Nile tilapia specimens (Oreochromis niloticus), each weighing approximately 1,000 grams. The samples were cultures for quantitative analysis on sheep blood agar (SBA) and chromID™ CPS® agar (CPS). Results: Eleven different bacterial species were identified on CPS and SBA plates. Gram-negative species were the most prevalent, while gram-positive Globicatella spp, Streptococcus spp and Enterococcus faecalis were also found. Pseudomonas aeruginosa species were isolated from all samples. Gram-positive Enterococcus faecalis was found in 70 and 60% of the skin and oral samples, respectively. Conclusion: For all samples studied, the microbial load was less than 100,000 CFU/g of tissue. This value is a cutoff standardized for the American Society of Microbiology to differentiate the causal agent from the colonizers. In light of this result and considering the absence of infectious signs in the fish samples, we conclude that the CFU values found in this study reflect a normal, non-infectious colonization/microbiota.